Comparative effectiveness of simultaneous administration of mifepristone and misoprostol versus interval regimen of mifepristone followed by misoprostol 12 hours apart in second trimester medical abortion - Saini, Arunima; Bedi, Preet kamal; Bhagat, Nisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: In second trimester abortion, medical methods are preferred. Prostaglandins are the most widely used. Amongst them, misoprostol is the most commonly used. Thus, the study was conducted to delineate the effectiveness of simultaneous administration of mifepristone and misoprostol versus interval regimen mifepristone followed by misoprostol 12 hours apart in second trimester medical abortion. Methods: It was a prospective, single centered, comparative study conducted on 50 patients in Department of Obstetrics and Gynaecology, GMC, Amritsar coming for second trimester abortion, either elective or emergency, with gestational age between 12-20 weeks. Initially, 53 patients were enrolled in the study, 3 patients dropped out at different stages of study. Finally, 50 patients were enrolled and divided into two groups of 25 patients each by 1:1 randomization. In Group-A, mifepristone 200 mg orally along with misoprostol 600µg vaginally were given simultaneously, followed by 400 µg vaginal misoprostol every 4 hours for a maximum of five doses in 24 hours. Group-B initially received mifepristone 200 mg per oral followed by 12 hours later misoprostol 400µg vaginally and then 400µg vaginal misoprostol every 4 hours for a maximum of five doses in 24 hours. Primary outcome measure was effectiveness of regimen in complete abortion, which was confirmed on pelvic ultrasound 1-week after the last dose. Secondary outcome measure was to compare the induction abortion interval (IAI), dose of misoprostol required and adverse drug reaction (ADR) among both the regimens. P-value <0.05 was taken as statistically significant. Results: Mean age in Group-A was 25.68±3.79 years while in Group-B was 23.40±2.73 years. Both the regimens had success rate of 76% for complete abortion. However, IAI in Group-A was 5.9±4.47 hours whereas in Group-B was 9.6±5.07 hours, which was statistically significant (p= 0.009). A statistically significant difference was also observed in the mean dose of misoprostol between two groups that is, 1000±200µg and 1425±437.41µg respectively (p=0.01). Gestational age was related to IAI from 13 to 17.6 weeks in both groups (p=0.01) while no significant relation was seen between them in more than 17.6 weeks of gestation (p=0.63). Conclusions: Simultaneous administration of mifepristone and misoprostol showed better results than interval regimen in term of significant lesser induction abortion interval, lower dosages of misoprostol required with comparable success rates.